Human capital and job satisfaction in transition economies: a comparative analysis of Hungary and Moldova - Ctitor, Mihaela; Suhajda, Csilla; Vinogradov, Szergej (Studia Mundi – Economica, 2025)
Based on survey data, collected in 2021, from 266 respondents (171 from Hungary and 95 from Moldova), this research utilizes statistical methods, including the Mann-Whitney U test, Kruskal-Wallis test, and Dunn-Bonferroni post hoc analysis, to examine variations across countries, generations, sectors, and organizational sizes.The results show no significant differences between Hungary and Moldova in the three human capital dimensions - Knowledge, Skills, and Competency - or job satisfaction, indicating the universal relevance of these factors across diverse socio-economic contexts. However, in Moldova, generational differences were observed in Competency levels, with Generation Z scoring lower than older cohorts, while no generational differences were found in Hungary. Sectoral analysis revealed higher job satisfaction among private-sector employees in Hungary compared to the public sector, whereas no such differences were evident in Moldova.Organizational size emerged as a significant factor influencing both human capital dimensions and job satisfaction in both countries. Micro-sized organizations reported the lowest scores, particularly in Moldova, while large organizations in Hungary showed higher levels of satisfaction, driven by better pay, benefits, and working conditions.The study underscores the importance of targeted interventions, such as skills development programs, reforms in the public sector, and tailored support for micro-sized organizations, to enhance employee satisfaction and optimize human capital utilization. These findings offer valuable insights into the relationship between human capital and job satisfaction in transition economies, providing actionable recommendations for policymakers and organizational leaders.